Personality and Epistemology: Cognitive Social Learning Theory as a Philosophy of Science - Jones, James W. (Zygon, 1989)
Abstract. Implicit in the cognitive social learning model of personality as articulated by Walter Mischel, Albert Bandura, and others, is an epistemology which emphasizes the activity of the mind in the construction of knowledge. Using Mischel's five person variables as an outline, the epistemic implications of this model of personality are developed and then illustrated by application to William James's typology of the religious personality and to the current debate over hermeneutic and empirical approaches to studying human behavior. This approach explicates the connection between personality characteristics and epistemological approaches in terms of cognitive social learning theory.